Direct-Contact Water-Loaded Metal-Dielectric Wall Diagonal Horn Applicators for Hyperthermia - Singh S.; Sahu B.; Singh S.P. (My University, 2025)
This paper describes simulation and/or experimental studies of specific absorption rate (SAR) and temperature distributions in a biological phantom (muscle)/realistic tri-layered bio-media without and with oval-/irregular-shaped tumour in direct contact with hybrid mode (water-loaded) metal-dielectric wall diagonal horn designed at 2450 and 915 MHz and their comparison among themselves with those due to respective conventional metal diagonal horns. The diagonal horns reported in this paper provide simple and effective means to enhance the penetration depth in the bio-medium/media. Moreover, effects on penetration depth and effective field size due to presence of oval- and irregular-shaped tumours in the tri-layered bio-media are also investigated at 915 MHz. It is demonstrated that desired temperature range 41 °C–45 °C can be achieved and maintained for 60 minutes with input power of 9 W at the frequency of 915 MHz for treating tumours at relatively greater depth. © 2018 IETE.